Successive Interference Analysis for 5G System at Mid-Band and High-Band Frequency - Kafle, Rudra Prasad; Maharjan, Ram Krishna; Pudasaini, Rupak (IRO Journal on Sustainable Wireless Systems, 2023)
This research study focuses on the impact of interference on different 5G system parameters such as modulation techniques (64-QAM, 256-QAM), channel models (AWGN, Rayleigh, and Rician), and MIMO (multiple input, multiple output) in terms of Bit Error Rate (BER). After the analysis of interference for each parameter, an analysis of interference by Short Range Devices (SRDs) on the 5G system network on the downlink channel is done. Finally, successive interference cancellation (SIC) for a 5G Non-Orthogonal Multiple Access (NOMA) system with Power Division Multiplexing (PDM) is applied. A 5G NOMA has higher spectral efficiency as compared to an Orthogonal Frequency Division Multiple Access (OFDMA), so it can fulfil the needs of the Internet of Things (IoT). SIC is implemented using PDM, where each user is assigned a certain power factor and generates a signal, the generated signal is superimposed and the New-Radio (NR) transmitter that transmits the superimposed signal. Finally, the signal is detected with and without SIC on the access side with SRDs as an interferer. After simulation and analysis of different 5G system parameters, it is found that the BER is decreased with an increase in the MIMO and is more applicable to the higher order modulation. With the SIC, the BER for the NOMA users decreased as compared to OFDMA users. The power coefficients for the stronger signal user (user 1) and weaker signal user (user 2) are 0.25 and 0.75 respectively.